Effect of Board Composition and Structure on performance of Kenya Football Premium League - Tuitoek, Paul; Tanui, John (KABARAK UNIVERSITY, 2018)
Football is an “industry” and clubs “businesses” characterized by competition for resources. The opportunities presented by expanding markets and the challenges of an environment characterized by increasing competition require that clubs successfully position themselves to build sustainable, competitive advantage. The main aim of the study was to analyze the effects of board composition and structure on performance of soccer management in Kenya Premium League. The study adopted descriptive research design taking 96 elected officials and 48 employees. The study used random sampling technique to select the respondents. Data was collected using both primary data collection tools. Structured questionnaires were administered to the selected respondents in order to elicit information related to governance structure of the Clubs whereas both structured questionnaire and secondary data collection form was used to collect information related to Kenya Football Premium League Performance. In spite of board membership being drawn from members who were not necessarily footballs, the board lacked wider representation in terms of gender, institutional representation like the government, age variability making the board not to have the face of Kenya, that is most clubs were aligned to specific tribe or counties, the idea which was a replica of their respective boards.
FULL TEXT
Keywords: Corporate Governance, Football Performance, Corporate Structures